Gaming experience on the mobiTop system: a collocated ad-hoc collaboration system - Teo, Rhun Ming; Ong, Beng Liang; Mohd Norowi, Noris; Mansor, Evi Indriasari; Dey, Prasenjit; Jamil, Izdihar (Penerbit Universiti Teknologi Malaysia, 2016)
This paper presents the study on the mobiTop system- a collocated multi-mobile system. The mobiTop system allows users to come together with their mobile devices in an ad-hoc manner to create one seamless and extended interactive display surface. The collocated multi-mobile system allows a group of people to play digital games together in an impromptu manner without having to buy an interactive tabletop equipment. This study investigates the user experience and system design of a collocated multi-mobile system when users play a collaborative game-based application using the mobiTop system. The findings show that the extended screen size of the mobiTop system enhanced the collaborative experience of the users. This study also highlights several design considerations to further improve such systems such as employing a faster network configuration, reducing the bezel effect, catering for dynamic device movements and making the object of interest more prominent and visible. With this understanding, this study present design guidelines to help designers create digital game-based multi-mobile systems for ad-hoc collaboration.